Health impacts of the M74 urban motorway extension: a natural experimental study. (November 2016) - Ogilvie, David; Foley, Louise; Nimegeer, Amy; Olsen, Jonathan; Mitchell, Richard; Thomson, Hilary; Crawford, Fiona; Prins, Richard; Hilton, Shona; Jones, Andy; Humphreys, David; Sahlqvist, Shannon; et al.
Abstract: Background: Increasing people's mobility can improve access to diverse opportunities, but new roads are associated with noise and community severance, and their effects on physical activity, injuries, and health inequalities are poorly understood. This study investigated how an urban motorway, opened in Glasgow in 2011, affected travel and activity patterns, injuries, and wellbeing in local communities, and how these impacts were experienced and brought about. Methods: This was a mixed-method, controlled, before and after natural experimental study. We conducted multivariable cohort, cross-sectional, and repeat cross-sectional analyses of survey responses from adults resident in the M74 corridor (intervention area) and two matched control areas, one surrounding the existing M8 motorway and one with no motorway (numbers by area: baseline [in 2005] 449, 431, 465, respectively; follow-up [in 2013] 430, 446, 467; cohort participants 126, 112, 127). We also conducted interrupted time-series analyses of police casualty data (STATS19 forms, 1997–2014; n=78 919), and thematic analysis of ethnographic data from 42 participants using constant comparison. Graded exposure measures based on the log distance of the motorway from each participant's home served as a further basis for controlled comparisons. The study was approved by the University of Glasgow Faculty of Medicine (ref FM01304) and Social Sciences (refs 400120077, 400130156, and 400130157) ethics committees. Findings: Living closer to the new motorway was associated with an estimated 3·6 unit (95% CI 0·7–6·6) reduction over time in mental wellbeing (mental component summary score [MCS-8] of SF-8) per unit of proximity in cohort analysis, and associated with a greater likelihood of car use at follow-up in repeat cross-sectional analysis (odds ratio 3·4, 95% CI 1·1–10·7). We found some evidence that participation in physical activity declined among cohort participants living closer to the existing M8 motorway (0·4, 0·2–0·9). We found no evidence of changes in active travel (survey data) or casualties (STATS19 data). Although the new motorway improved connectivity for individuals with more dispersed social networks and access to a motor vehicle, the impacts on those with neither of them were more complex and sometimes negative. Changes in community composition and cohesion, and perceptions of personal safety, were widely perceived as more important influences than was the opening of the motorway. Interpretation: Although the study identified both benefits and harms, overall these findings highlight the potential for new major road infrastructure to add further burdens to already disadvantaged communities, exacerbating inequalities and contributing to poorer health outcomes. Funding: National Institute for Health Research (NIHR) Public Health Research Programme. The funder had no role in the design of the study, the analysis or interpretation of the data, the writing of the abstract, or the decision to submit it for publication.